Changes of coastline and tidal flat and its implication for ecological protection under human activities: Take China’s Bohai Bay as an example - Yong Li; Ming-zheng Wen; Heng Yu; Peng Yang; Fei-cui Wang; Fu Wang (China Geology)
The change processes and trends of shoreline and tidal flat forced by human activities are essential issues for the sustainability of coastal area, which is also of great significance for understanding coastal ecological environment changes and even global changes. Based on field measurements, combined with Linear Regression (LR) model and Inverse Distance Weighing (IDW) method, this paper presents detailed analysis on the change history and trend of the shoreline and tidal flat in Bohai Bay. The shoreline faces a high erosion chance under the action of natural factors, while the tidal flat faces a different erosion and deposition patterns in Bohai Bay due to the impact of human activities. The implication of change rule for ecological protection and recovery is also discussed. Measures should be taken to protect the coastal ecological environment. The models used in this paper show a high correlation coefficient between observed and modeling data, which means that this method can be used to predict the changing trend of shoreline and tidal flat. The research results of present study can provide scientific supports for future coastal protection and management.©2024 China Geology Editorial Office.